Selective leaching of metals from spent Ni-Mo hydrodesulphurisation catalysts using microwave-assisted method - Isabel S. S. Pinto (2013)
The aim of this work was to study a two-stage selective leaching of Mo and Ni from a hydrodesulphurisation alumina-based spent catalyst, using microwave-assisted conditions, and compare to a conventional process (thermostatic bath). First-stage was performed using NaOH solutions for studying selective recovery of Mo. In both conventional and microwave-assisted leaching, Mo recovery was higher for 0.5 M NaOH, but a more selective leaching of Mo was obtained when 0.25 M NaOH was used due to the lower extraction of Al. After 4 cycles, 30 s of microwave heating each, using 0.25 M NaOH solution, 89 and 6% of Mo and Al, respectively, were removed, resulting in a more selective and enhanced Mo leaching than the conventional method. For Ni recovery, extraction was firstly tested with H2SO4. Using 0.8 M H2SO4, results after 4 cycles (30 s) of microwave heating were similar to the ones obtained during conventional leaching (4h, 80°C): up to 95 and 68% extraction of Ni and Al, respectively. EDTA aqueous solutions were also tested to try to increase Ni selectivity. Thermostatic bath tests did not promote Ni dissolution (40%), while for microwave-assisted leaching, the best result was obtained for 4 cycles (60 s) and 0.1 M EDTA, with recoveries of Ni and Al of 80 and 2.8%, respectively. In conclusion, the application of a microwave-assisted method for metal leaching from spent HDS catalysts, resulted in higher dissolution of the target metals (Mo and Ni) using more mild conditions, which allowed higher selectivity, as well as lower processing times.